Solar-powered electric car: validity and effectivity of prop in energy conversion learning - Rizal, Rahmat; Aripin, Haji; Joni, I Made (Intelektual Pustaka Media Utama, 2024)
The research aimed to describe the development of solar electric cars as a prop in energy conversion learning using the analyze, design, develop, implement, and evaluate (ADDIE) model and to ascertain the effectiveness of an electric car as a prop in energy conversion learning. Utilization of prop in the learning process is one way to support the development of knowledge, skills, and basic needs for delivering material, concepts, and physics information. This research is a descriptive study involving media and pedagogical experts and 40 students of the university in Tasikmalaya. Data collection techniques were carried out through the study of literature, expert validation, and student perception questionnaires. Expert validation and student perception were obtained by using a Likert scale. The expert judgment results were processed using the V value equation developed by Aiken. The results showed a value of 1, meeting the minimum validation requirements. The students also had positive responses to a prop. They have new experience learning in energy conversion and have good media to help their comprehension. It has a significant impact on helping students to achieve their learning goals.